Pharmacological Activities of Three Kinds “Kayu kuning”: Arcangelisia flava, Fibraurea tinctoria, and Coscinium fenestratum – an Short Review - Riski Sulistiarini; Andreanus A Soemardji; Elfahmi; Maria Immaculata Iwo (Journal of Tropical Pharmacy and Chemistry, 2020)
The literature-based review was constructed discussing three types of yellow woods plant from Indonesia, including Arcangelisia flava, Fibraurea tinctoria, and Coscinium fenestratum. Yellow wood plants are widely used as traditional medicine due to its activities that were pharmacologically studied. Those activities include antiplasmodial, cytotoxic, antioxidant, toxicity, antidiabetic, anticolestroleia, antihypertensive to liver activity, and health-behavior changes in experimental animals.